Faktor-faktor yang mempengaruhi keinginan berhenti kerja di kalangan pekerja sokongan di Jabatan tanah dan Survei, Sarawak - Halifah, Abdul Hamid (Universiti Malaysia Sarawak (UNIMAS), 2005)
This study aimed to determine factors that influence intention to quit among the Land and Surveys, Sarawak supporting staff. The factors investgated were job stressors, job stress, job satisfaction, commitment, locus ofcontrol and supervisory support. Questionnaires were used to collect information from 56 respondent in Land and Surveys, Sarawak. The findings showed that there were no significant relationships between job stressor, locus of control and supervisory support and intention to quit. Besides that there was a positive relationship between job satisfaction and intention to quit. The findings also showed that there were negative relationships between job stress and commitment and intenton to quit. Human resource practioner should give intention to reduce job stress and increase job satisfaction and job commitment. It is also suggested that top management should provide stress management programme to their employees, involve employees in decision making process and share information and views with them.